Characteristics of patients with increasing COPD assessment test scores within 3 years. (October 2017) - Irie, Hidehiro; Chubachi, Shotaro; Sato, Minako; Tsutsumi, Akihiro; Nakachi, Ichiro; Miyao, Naoki; Nishio, Kazumi; Nakamura, Hidetoshi; Asano, Koichiro; Betsuyaku, Tomoko
Abstract: Background: The chronic obstructive pulmonary disease (COPD) Assessment Test (CAT) is a subjective measure of quality of life. The aim of this study was to examine the characteristics of COPD patients with increasing CAT scores within 3 years. Methods: Keio University and its affiliate hospitals conducted an observational COPD cohort study over 3 years. St. George's Respiratory Questionnaire (SGRQ) and CAT were completed at baseline and annually thereafter. Patients who had at least 3 CAT scores were included (n = 315). The ΔCAT score/year and ΔSGRQ score/year were calculated by the slope between each of the measures and the date of measurement. Results: The median ΔCAT score/year was 0.4, and ΔCAT score/year was significantly correlated with ΔSGRQ total score/year. Using an annual cut-off CAT score of +2 points, patients who deteriorated (n = 79) were older, had lower %FEV1, and more severe emphysema on computed tomography scan at baseline than patients who did not deteriorate. The baseline value was not a determinant of subsequent changes in the CAT score. Longitudinal changes in the CAT score were positively correlated with those in the SGRQ score. Conclusions: Old age and severe COPD, not the CAT score at one time point, predicted worsening quality of life. Highlights: Characteristics of COPD patients with increasing CAT scores within 3 years was investigated. Patients who deteriorated CAT scores were older, had lower %FEV1, and more severe emphysema. Baseline CAT value was not a determinant of subsequent changes in the CAT score. Longitudinal changes in the CAT score were positively correlated with those in the SGRQ score.